Enhanced CYP2C19-mediated drug-drug interaction risk with escitalopram in geriatric populations - Byoun, Seonyoung; Heo, Dong-Gyu; Lee, Minsoo; Lee, Ryunghwa; Li, Yuanyuan; Lee, Ju-Yeun; Hong, Eunjin; Lee, Wooin (Frontiers in Pharmacology, 2026)
IntroductionEscitalopram (S-CIT) is commonly prescribed for depression and anxiety in older patients. Previous research has reported that the effect of CYP2C19 polymorphism on S-CIT pharmacokinetics is more pronounced in older adults than in young adults. The current study investigated whether older adults taking S-CIT face a greater risk for CYP2C19-mediated drug-drug interaction (DDI) than young adults.MethodsUsing a physiologically-based pharmacokinetic (PBPK) model, we quantitatively compared the risk of CYP2C19-mediated DDIs in older adults taking S-CIT with any of four CYP2C19 inhibitors (omeprazole, esomeprazole, fluconazole, and fluoxetine). These CYP2C19 inhibitors were selected based on their prevalence of co-administration with S-CIT, as determined by a retrospective analysis of the 2019 Korean National Health Insurance Service senior cohort database.Results and DiscussionOur PBPK modeling-based simulations predicted that the extent of DDI incurred by S-CIT would be greater in older adults than in young adults and vary significantly by CYP2C19 phenotypes (extensive, intermediate, and poor metabolizers). Based on the prediction results, we propose CYP2C19 phenotype-guided S-CIT dosing strategies for older adults. Implementing the proposed dosing recommendation may reduce the incidence of potentially inappropriate use of medication and adverse events in older adults prescribed S-CIT.